Graph-Based Engineering Systems - A Family of Software Applications and their Underlying Framework - Wrobel, Gregor; Ebert, Ralf-Erik; Pleßow, Matthias (Electronic Communications of the EASST, 2007)
In various engineering disciplines visual modeling techniques are used for the definition as well as representation of complex systems. Besides the pictorial illustration, the included structural information is often used for application-specific procedures. This paper presents a few engineering systems for quite different application fields, but they use a common graph-based model. This model is part of a framework that underlies these applications. Various kinds of applications can be developed on the basis of this framework by means of configurations and extensions. The development of new applications is supported by convenient assemblies of suitable system functions and layout methods as well as by integration of application functionalities. The introduced framework is the basis for a product line of graph-based engineering systems.